Exploring the emotional dimension of visitors' satisfaction at cultural events - Christou, Prokopis A.; Sharpley, Richard; Farmaki, Anna (My University, 2018)
Cultural events have emerged as a destination instrument for sharing local folk culture with visitors, aspiring to provide them with satisfying experiences at the same time as conveying socioeconomic benefits to the local community. However, studies of the visitor satisfaction process as a measure of the success of staging a cultural event remain noticeably lacking. Adopting an ethnographic approach, this article investigates visitor satisfaction by considering the emotional dynamics involved-a psychological dimension that remains largely overlooked within the tourism context. Fieldwork findings reveal the important role of senses in this process and pinpoint precise emotions that impact on (dis)satisfaction and intentions. Based on the research outcomes, the article then proposes a model conceptualizing this process that is of relevance beyond the specific context of events. The study envisages a tighter link between the fields of tourism and psychology, given the potentially rewarding outcomes this might yield.
Keywords: Cultural events; Cyprus; Emotions; Psychology; Senses; Tourism; Visitor satisfaction